Analisis Kelong Sisila-Sila dalam Syair "Pakkiok Bunting" di Desa Songkolo Kabupaten Gowa (Kajian Hermeneutika Paul Ricoeur) - Illang, Illang; Daeng, Kembong; Hajrah, Hajrah (Nuances of Indonesian Language, 2024)
This research aims to reveal  stages of meaning of kelong Sisila-sila in the poetry of Pakkiok Bunting, Songkolo Village, Gowa Regency. by using Paul Ricoeur's hermeneutical theory. Hermeneutics is an important element in understanding or providing meaning from a text. This theory uses three stages, namely objective meaning, reflective meaning and existential meaning. The method was designed using qualitative descriptive analysis research. The data is sourced from the kelong sisila-sila in the pakkiok bunting poem, Songkolo Village, Gowa Regency. Data collection techniques were carried out using interviews, reading and listening, taking notes and documentation. The results of the research show that the analysis of the kelong Sisila-sila in the pakkiok bunting poetry of Songkolo Village, Gowa Regency found 28 symbol on stages of objective, reflective and existential meaning. . In this meaning it contains advice or pap put toriolo which is useful for the people who listen. Kelong Sisila-sila in the poem Pakkiok Bunting is believed by the Songkolo people to be oral literature which reflects that Makassar culture must be respected, especially for the younger generation in developing Makassar literature.Keywords: Kelong Sisila-sila, Pakkiok Bunting, Paul Ricoeur's Hermeneutics,Penelitian ini bertujuan mengungkap tahapan makna yang ada pada kelong sisila-sila dalam syair pakkiok bunting Desa Songkolo Kabupaten Gowa. dengan menggunakan kajian teori hermeneutika Paul Ricoeur. Hermeneutika merupakan unsur penting dalam memahami atau memberikan makna dari sebuah teks. Teori ini menggunakan tiga tahapan yakni makna objektif, makna reflektif dan makna eksistensial. Metode didesain dengan penelitian kualitatif deskriptif analisis. Data bersumber pada kelong sisila-sila dalam syair pakkiok bunting Desa Songkolo Kabupaten Gowa. Teknik pengumpulan data dilakukan dengan wawancara, baca-simak, catat, dan dokumentasi. Hasil penelitian menunjukkan bahwa analisis kelong sisila-sila dalam syair pakkiok bunting Desa Songkolo Kabupaten Gowa ditemukan 28 simbol Tahapan makna objektif, reflektif dan eksistensial. Dalam makna tersebut mengandung nasehat atau pappasang toriolo yang berguna bagi masyarakat yang mendengarkan.  Kelong sisila dalam syair pakkiok bunting dipercaya oleh masyarakat Songkolo merupakan suatu sastra lisan yang mencerminkan bahwa budaya Makassar harus dihargai keberadaannya khususnya bagi generasi muda dalam mengembangkan sastra Makassar.Kata Kunci: Kelong Sisila-sila, Pakkiok Bunting, Hermeneutika Paul Ricoeur